Co wspólnego ma coaching z lekcjami języka polskiego? - Karolczyk-Kozyra, Agata (Tomorrow's school? Tradition and (r)evolutions in education, 2023)
The aim of the article is to raise the issue of educational coaching and its use during Polish language lessons in a secondary school. The author explains the concept of coaching and presents its genesis. It lists the characteristics of a good coach, paying attention to the competences of a modern teacher. It also presents exemplary coaching methods and techniques that he uses in the work of a Polish language teacher.